RESEPSI KHALAYAK GENERASI Z TERHADAP MAKNA KEHILANGAN DALAM LIRIK LAGU BERTEMA KESEDIHAN “LIHAT KEBUNKU (TAMAN BUNGA)” KARYA AKU JEJE - Muhammad Krisna Rachmatullah; Mohammad Ichlas El Qudsi (Jurnal Komunikasi & Media Digital, 2026)
This research is about the meaning of loss represented in the lyrics of the song “Lihat Kebunku (Taman Bunga)” by Aku Jeje and how this meaning is interpreted by Generation Z audiences, with the purpose of analyzing the reception of Generation Z audiences toward the meaning of loss in the song lyrics through Stuart Hall’s reception analysis approach. This research is motivated by the increasing consumption of emotionally themed music among Generation Z, which is often used as a medium for reflecting personal experiences of loss in daily life. The method used is a qualitative approach. The analysis is conducted using Roland Barthes’ semiotic theory to identify denotative, connotative, and myth meanings in the song lyrics. In addition, Stuart Hall’s reception analysis is used to understand the audience’s decoding positions. The data were collected through lyric text analysis and interviews with Generation Z informants. The results show that the meaning of loss in the song lyrics is constructed through a series of sign relations that describe emotional attachment, relational change, and the process of accepting separation. The meaning is interpreted as relational loss in individual life experiences. The reception results show variations of interpretation categorized into dominant hegemonic position and negotiated position. These differences are influenced by personal experiences, emotional conditions, and social backgrounds of each informant. This study confirms that meaning in lyrics is not fixed. Meaning is constructed through the interaction between text and audience experience in the decoding process.